Estimated Dose to Family Members of Patients Treated with Radioiodine - Zdraveska Kochovska, Marina; Spasic Jokic, Vesna; Majstorov, Venjamin; Dugonjic, Sanja (Oxford University Press (OUP), 2017)
Patients who receive therapeutic amount of 131I are potentially significant source of radiation to their family members and general public. The aim of this study was to estimate effective dose to family members of patients treated with radioiodine, released after 3 d of hospitalization and to compare with dose constraints proposed by international recommendations. The thermoluminescence dosemeters (TLD 100) and Radiation Dose Assessment Resource (RADAR) software were used for assessment of effective doses to 60 family members of the same number of hyperthyroid and thyroid carcinoma patients. Estimated effective doses were well below recommended dose limits except in a few cases. RADAR-calculated doses were higher than doses measured by TLD. Hyperthyroid patients should continue to be treated on outpatient basis but they should be well informed for their further behavior to provide minimal radiation hazard for the people in their environment.